Use of Augmented Reality in Biology Learning - Cartono Cartono (Educare: Journal Educational and Multimedia, 2024)
Augmented Reality (AR) technology is the latest innovation that can be an effective solution for educators to provide innovative, informative and interesting learning experiences. AR allows the presentation of virtual objects in 3D virtual form that is integrated with real environments in real time, so that it can transform abstract concepts into experiences that are more real and can be applied directly. This research aims to analyze the use of Augmented Reality in Biology Learning at school. This research uses a qualitative approach with descriptive methods. The research results show that the use of Augmented Reality (AR) technology in biology learning has a significant positive impact. The use of AR allows students to explore biological concepts in more depth through interactive 3D object visualization. Students respond positively to immersive and engaging learning experiences, which motivate them to actively engage. AR's ability to present biological concepts concretely makes it easier for students to understand complex material. In addition, AR also provides opportunities for collaboration, independent exploration, and integration of modern technology in the biology learning process, making it an effective tool for achieving learning goals in the high-tech era.